The Side Effects of Central Bank Independence. Issue 4 (22nd December 2020) - Aklin, Michaël; Kern, Andreas
Abstract: Central bank independence (CBI) solves the time inconsistency problem faced by policymakers with respect to monetary policy. However, it does not solve their underlying incentives to manipulate the economy for political gains. Unable to use monetary policy, and often limited in their ability to use fiscal spending, governments can resort to financial deregulation to generate short‐term political benefits. We show qualitatively and quantitatively that governments systematically weaken financial regulations in the aftermath of CBI, and that the effect of CBI is separate from an ideological shift toward liberalization. Our findings suggest that the growing financialization of the economy experienced by many countries over the last few decades is partly a by‐product of central bank independence.